2007
DOI: 10.1093/humrep/dem142
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D reserve is higher in women with endometriosis

Abstract: BACKGROUND: An immune-mediated defect in recognition and elimination of endometrial fragments refluxed in the peritoneal cavity has been hypothesized to play a crucial role in endometriosis development. Since vitamin D is an effective modulator of the immune system, we have hypothesized that the vitamin D status may have a role in the pathogenesis of endometriosis. METHODS: Women of reproductive age selected for surgery for gynecological indications were enrolled in this prospective cohort study. Serum levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 25 publications
3
52
0
9
Order By: Relevance
“…(33), but conflict with Somigliana and cols. 's findings that women with endometriosis had higher 25(OH)D concentrations, and that the severity of the endometriosis was associated with the 25(OH)D concentrations (34). Moreover, another study found high concentrations of 1,25(OH) D in women with endometriosis, although there was no significant difference when their concentrations were compared to 25(OH)D concentrations in women without endometriosis (35).…”
Section: Resultsmentioning
confidence: 96%
“…(33), but conflict with Somigliana and cols. 's findings that women with endometriosis had higher 25(OH)D concentrations, and that the severity of the endometriosis was associated with the 25(OH)D concentrations (34). Moreover, another study found high concentrations of 1,25(OH) D in women with endometriosis, although there was no significant difference when their concentrations were compared to 25(OH)D concentrations in women without endometriosis (35).…”
Section: Resultsmentioning
confidence: 96%
“…Levels of the vitamin were reported to be increased in endometriosis [8]. The relationship between vitamin D and steroidogenesis was affected by calcium homeostasis and the direct regulation of the expression of the aromatase gene [9].…”
Section: Introductionmentioning
confidence: 99%
“…A study on the effects of vitamin D and calcium intake on endometriosis by Somigliana et al (2007) indicated that endometriosis is associated with high vitamin D intake (14).…”
Section: Discussionmentioning
confidence: 99%